Nanosized Technological Approaches for the Delivery of Poorly Water Soluble Drugs: Delivery of poorly water soluble drugs - Basavaraj K. Nanjwade; Ganesh K. Derkar; Hiren Bechra; F. V. Manvi (Iranian Journal of Pharmaceutical Sciences, 2010)
A major hurdle in pharmaceutical formulation is water insolubility of most of drugs affecting their stability and bioavailability. If the drug is also insoluble in organic medium, it is difficult to deliver it in a sufficiently bioavailable form and hence it is a great challenge to formulation researchers to overcome such difficulty. Although some approaches are available for enhancing the dissolution of poorly soluble drugs, there has been certain draw backs like use of organic solvents, low drug loading and large doses. However, a new solution to poorly water soluble drug candidates is now available, i.e. nanonisation that leads to much more soluble, more biologically available and safer dosage form of poorly soluble and poorly bioavailable drugs. Controlled release of these drugs is also possible by forming nanostructured matrices. In this article, a brief description of production methods of drug nanoparticles and commercialized methods are presented along with brief overview on second generation of drug nanocrystal (Smart crystal technology), controlled release of hydrophobic drugs and recent works thereof are also presented.